2012
DOI: 10.1021/cg201112j
|View full text |Cite
|
Sign up to set email alerts
|

BiOCl Sub-Microcrystals Induced by Citric Acid and Their High Photocatalytic Activities

Abstract: Bismuth oxychloride (BiOCl) sub-microcrystals with tunable morphologies from nanoflakes to hollow microspheres (HMSs) have been synthesized by hydrolyzing a hierarchical precursor (BiCl 3 ) in a solution of water and ethanol with the addition of poly(vinylpyrrolidone) (PVP) and citric acid. The obtained BiOCl possessed sub-microcrystals from single crystals to polycrystals. The formation of the nestlike and hollow structure was found to be induced by citric acid and PVP. The crystal growth and morphology contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
146
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(154 citation statements)
references
References 57 publications
8
146
0
Order By: Relevance
“…It is its size, shape and surface structure which will, ultimately, control their optical and photocatalytic properties and therefore its suitability to distinct purposes. For example, BiOCl has shown ability to water splitting reaction under solar light irradiation [1][2][3] , photocatalytic activity to the degradation of dyes and other pollutants under ultra-violet (UV) and visible radiation [4][5][6][7][8][9][10][11] , UV photodetectors 12 , to be used as catalyst for air electrode of aluminium-air batteries 13 and as an anode material for sodium-ion batteries. 14 BiOCl has a tetragonal structure, formed by layers of [Bi2O2] 2+ intercalated with a double layer of chloride ions accommodated in the interlayers, with interlayer distance of 7.38 Å.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is its size, shape and surface structure which will, ultimately, control their optical and photocatalytic properties and therefore its suitability to distinct purposes. For example, BiOCl has shown ability to water splitting reaction under solar light irradiation [1][2][3] , photocatalytic activity to the degradation of dyes and other pollutants under ultra-violet (UV) and visible radiation [4][5][6][7][8][9][10][11] , UV photodetectors 12 , to be used as catalyst for air electrode of aluminium-air batteries 13 and as an anode material for sodium-ion batteries. 14 BiOCl has a tetragonal structure, formed by layers of [Bi2O2] 2+ intercalated with a double layer of chloride ions accommodated in the interlayers, with interlayer distance of 7.38 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its layered structure this material can be prepared in a wide range of sizes and shapes, with sheet and plate-like morphologies the most commonly reported [5][6][7]10,[14][15][16] , however hexagonal prisms 8 and hierarchical structures resulting from distinct assembling of nanosheets are also reported. 4,7,9,11 BiOCl is a semiconductor with wide band gap and indirect band gap energy (Eg). Values ranging from 2.25 to 3.5 eV have been reported in the literature 1,2,4,6,9,10,17 , depending mostly on particle size, crystal structure and surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hierarchical nanostructured BiOCl with controllable sizes and morphologies is desired for the purpose of enhancing photocatalytic performance. 6 8 Hereby, two dimensional (2D) [9][10][11] and three dimensional (3D) [12][13][14] BiOCl nanostructures have been prepared through a variety of synthetic protocols. 3D hierarchical nanostructures have the advantages of both microstructure and nanostructure, such as the high crystallinity, high surface-tovolume ratio, strong light-harvesting ability, and abundant electronic transport paths, ensuring the improvement of photocatalytic capability.…”
Section: Introductionmentioning
confidence: 99%
“…15 Rhodamine B (RhB). 12 Lei et al reported that 3D hierarchical structured BiOCl showed higher photocatalytic efficiency towards methyl orange than 2D nanoplates. 13 Zhu et al demonstrated that 3D BiOCl hierarchitectures were beneficial for photocatalysis in comparison with BiOCl nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As we all know, controlling the size of materials at the nanometer scale could induce the emergence of new physical and chemical properties. As the size of the materials decrease, the percentage of surface atoms with more dangling bonds and the surface-to-volume ratio increase dramatically.…”
Section: Introductionmentioning
confidence: 99%